The Lind-Lehmer Constant for cyclic groups of order less than 892,371,480 - Pigno, Vincent; Pinner, Christopher G. (My University, 2013)
We determine the Lind–Lehmer constant for the cyclic group Zn when n is not a multiple of 892,371,480=2³⋅3⋅5⋅7⋅11⋅13⋅17⋅19⋅23.
Keywords: Mahler measure; Lind’s Lehmer Problem; Finite Abelian groups